The effect of office environment towards employees job productivity at Johor Corporation, Johor / Nurul Atiqah Yusof - Yusof, Nurul Atiqah (2014)
In today's competitive business environment, corporations can no longer afford to waste the potential of their workforce. There are important factors in the employee's workplace that influence significantly on their level of motivation and productivity, The main objective of the study is to understand the relationship between the employees' productivity and their physical work environment. The private sector corporations of Johor have been chosen as the population for the study. The results of the study show that office environment has a slightly impact on the employees' productivity.